Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/cryst10040283
|View full text |Cite
|
Sign up to set email alerts
|

Triple Solutions and Stability Analysis of Micropolar Fluid Flow on an Exponentially Shrinking Surface

Abstract: In this article, we reconsidered the problem of Aurangzaib et al., and reproduced the results for triple solutions. The system of governing equations has been transformed into the system of non-linear ordinary differential equations (ODEs) by using exponential similarity transformation. The system of ODEs is reduced to initial value problems (IVPs) by employing the shooting method before solving IVPs by the Runge Kutta method. The results reveal that there are ranges of multiple solutions, triple solutions, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
(51 reference statements)
0
9
0
Order By: Relevance
“…Meanwhile the decreasing trend of Nusselt number corresponds to the increase in values of b and β is observed, as shown in Figure 17. These observations are expected, since the fluid temperature at the surface is inversely proportional to Nusselt number, as denoted in Equation (24). As a result, the decrease in value of surface temperature leads to the increase in Nusselt number.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…Meanwhile the decreasing trend of Nusselt number corresponds to the increase in values of b and β is observed, as shown in Figure 17. These observations are expected, since the fluid temperature at the surface is inversely proportional to Nusselt number, as denoted in Equation (24). As a result, the decrease in value of surface temperature leads to the increase in Nusselt number.…”
Section: Resultsmentioning
confidence: 66%
“…The unsteady state of mixed convection flow of micropolar fluid moving along an inclined stretching plate has been scrutinized by Kasim et al [12]. Furthermore, some interesting studies regarding fluid flow and heat transfer for various aspects have been investigated, as reported in [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…According to Lund et al [29,30], Hamid et al [31], and Mustafa et al [32], the stability analysis of the dual solutions is verified by perturbing the steady solution by using following functions…”
Section: Stability Analysismentioning
confidence: 99%
“…The boundary layer flow of micropolar fluid over a sheet, shrinking exponentially, was then discussed by Aurangzaib et al 27 It was concluded in this study that strong suction is required for the solution to exist, and dual solutions were found at certain suction rates. However, Lund et al 28 prove that triple solutions exist in this problem. Recently, Lund et al 3 extended the study by analysing the effects of the magnetic field, viscous dissipation and Joule heating to the fluid flow.…”
Section: Introductionmentioning
confidence: 99%